Islamic Movement Global Jihad: Analysis of Online Media Framing - Imam Suprabowo (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
In 2015-2016, news in online media related to jihad issues developed significantly, marked by the emergence of various religious sites. However, in the Indonesian context, there has not been much literature that specifically explores the relationship between online media ideology and religious issues. To fill this gap, this article aimed to analyze the framing of Islamic online media related to the issue of jihad. This research used descriptive qualitative to analyze the issue of jihad in online media. The Entman framing theory applied in this study, including jihad as war, improving welfare, dangerous jihad, enforcement of Islamic law and jihad against the authorities. The study focused on four Islamic sites of Arrahmah.com, Hidayatullah, Hizb ut-Tahrir Indonesia, NU online and Republika online from 2015-2016. The results showed that Arrahmah portrayed jihad in the framework of war to uphold Allah’s law, while Hidayatullah.com framed jihad as a real war. Hidayatullah focused on liberating Muslim lands related to conflicts in the Rohingya and Palestine. In comparison, NU Online uplifted jihad for the welfare of the community. One of the biggest frameworks was to defend the state for the welfare of society, eradicating ignorance and poverty, and anti-corruption jihad. In the fourth media, Republika online emphasized social welfare and jihad and pushed it over other news. From the analysis, the issue of jihad was framed differently by online Islamic media. Consequently, the difference was in the selection of events, the frequency of news titles, the emphasis on the selection of words, examples and illustrations.